2020
DOI: 10.1097/md.0000000000023182
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin multidimensional health literacy questionnaire for patient supporting groups

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
5
2
Order By: Relevance
“…The lowest score was with subclass 3 (appraisal) (9.77 ± 2.39). These findings are with our previous report [9] that the lowest score of MMHLQ was with the dimension of appraisal (10.66 ± 2.33 of subscale 3). In general, patients or families who expressed a desire to join PSG exhibited an open-minded personality and a willingness to acquire new knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lowest score was with subclass 3 (appraisal) (9.77 ± 2.39). These findings are with our previous report [9] that the lowest score of MMHLQ was with the dimension of appraisal (10.66 ± 2.33 of subscale 3). In general, patients or families who expressed a desire to join PSG exhibited an open-minded personality and a willingness to acquire new knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Health literacy encompasses 5 dimensions, which include knowledge, numeracy, navigation, communication, and decision making. [7] In our previous study, [9] we have found that the dimension of understanding had the highest score, while the dimension of appraisal had the lowest score. Elderly participants exhibited weaker health literacy, particularly in the dimension of the appraisal.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For four out of the five dimensions of health literacy, the scores were insufficient; of these, the lowest score was for the dimension “evaluating health information”. Among the five dimensions of health literacy, that is, (1) accessing health information, (2) understanding health information, (3) evaluating health information, (4) applying health information and (5) communication and interaction (Wu et al., 2020), only the dimension of communication and interaction showed an adequate level. The ability to communicate and interact with health care providers was consistent with that observed in patients with hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Later, we cataloged these scores into four levels: inadequate (≤25), limited/problematic (25 ≤ 33), sufficient (33 ≤ 42), and excellent (42 ≤ 50). Several studies have demonstrated that the MMHLQ is an adequate tool for health literacy ( 16 – 18 ). In addition, the Cronbach's alpha reliability of MMHLQ was 0.79 (alpha if item deleted was 0.77–0.94) which represented an acceptable range.…”
Section: Methodsmentioning
confidence: 99%